Evaluation of hearing protection used by police officers in the shooting range - Guida,Heraldo Lorena (2014)
Introduction: Impact noise is characterized by acoustic energy peaks that last less than a second, at intervals of more than 1 s. Objective: To quantify the levels of impact noise to which police officers are exposed during activities at the shooting range and to evaluate the attenuation of the hearing protector. Methods: Measurements were performed in the shooting range of a military police department. An SV 102 audiodosimeter (Svantek) was used to measure sound pressure levels. Two microphones were used simultaneously: one external and one insertion type; the firearm used was a 0.40 Taurus® rimless pistol. Results: The values obtained with the external microphone were 146 dBC (peak), and a maximum sound level of 129.4 dBC (fast). The results obtained with the insertion microphone were 138.7dBC (peak), and a maximum sound level of 121.6 dBC (fast). Conclusion: The findings showed high levels of sound pressure in the shooting range, which exceeded the maximum recommended noise (120 dBC), even when measured through the insertion microphone. Therefore, alternatives to improve the performance of hearing protection should be considered.